A cobalt diffusion-based integrated heterogeneous alloy rotary file forming method

CN122956029APending Publication Date: 2026-10-23赣州锐科合金材料有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611450453.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-18
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]本发明的目的就是为了弥补现有技术的不足,提供了一种基于钴扩散的异质合金旋转锉一体成型方法,通过粉末配制球磨、非对称振动压制、洁净同轴装配、梯度真空烧结及精密加工检测的完整流程,实现硬质合金刀头与韧性合金夹持柱的一体化制备,该方法依托钴元素界面扩散形成致密冶金结合层,解决传统分体制备结合薄弱、收缩不匹配、成型精度差等问题,让刀头耐磨特性与夹持柱韧性优势协同发挥,整体工艺简化生产环节,提升坯体密度均匀性与成品同轴度,保障旋转锉高速运转稳定性与结构强度,可广泛用于精密加工领域,有效提升工具服役寿命与加工可靠性,推动切削工具制备技术升级

Benefits of technology

[0021]一、本发明通过搭配硬质合金刀头与韧性合金夹持柱的粉末体系,配合专属球磨工艺提升粉末均匀性与成型性,采用非对称振动压制技术制备匹配嵌合的预成型体,精准调控两类坯体的收缩特性,避免烧结过程中出现变形、开裂问题,依托阶梯嵌合结构增大界面结合面积,经梯度真空烧结实现钴元素的充分界面扩散,在结合区域形成连续致密的过渡层,消除界面缝隙与结合薄弱点,让刀头的高硬度、高耐磨特性与夹持柱的高韧性、抗弯折特性有机融合,一体成型工艺省去传统二次连接工序,保障装配同轴度与界面结合稳定性,提升旋转锉高速旋转时的结构稳固性,优化切削使用性能,延长工具整体服役寿命,同时简化生产环节,提升加工成型的可靠性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122956029A_ABST
    Figure CN122956029A_ABST
Patent Text Reader

Abstract

The application discloses a cobalt diffusion-based integrated forming method of a heterogeneous alloy rotary file, and relates to the technical field of cutting tool preparation.The specific steps of the method are as follows: first, WC-Co hard alloy tool bits and Ni-Co-based tough alloy clamping column powders are prepared and vacuum ball milled respectively; then, pre-formed bodies with specific structures are formed by asymmetric vibration pressing; then, coaxial assembly and cleaning are performed; subsequently, gradient vacuum sintering is performed; finally, the sintered blanks are precisely processed to remove the oxide layer burrs, the blade parts and the handle parts are precisely processed, and the performance parameters of the finished products are detected; by optimizing the powder system, ball milling and pressing processes, and by adopting stepwise embedding and gradient vacuum sintering, the characteristics of the tool bits and the clamping column are organically integrated; the post-processing process is also optimized, the influence of impurities is eliminated, the sintering quality is ensured, and through precise processing and multi-dimensional detection, metallurgical bonding is realized, the tool performance, safety and efficiency are improved, and the service life is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cutting tool manufacturing technology, specifically to a method for integrally forming a heterogeneous alloy rotary file based on cobalt diffusion. Background Technology

[0002] Rotary files, as core cutting tools in the field of industrial precision machining, are widely applicable to the grinding, cutting, and shaping of various materials. Their performance directly determines the machining accuracy and work efficiency. The industry typically uses cemented carbide to make the cutting head to ensure cutting hardness and wear resistance, and combines it with tough alloys to make the clamping posts to meet the requirements of bending resistance and impact resistance of the shank. The combination of dissimilar alloys has become the mainstream material selection direction for rotary files. Powder metallurgy and sintering are the core processes for manufacturing this type of tool. How to achieve efficient combination of two types of alloys and ensure the overall structural stability is a key technical direction for the industry to overcome. As the requirements for precision machining continue to increase, the market has put forward higher standards for the high-speed operation stability, interface bonding strength, and service life of rotary files. Traditional manufacturing processes are difficult to balance the performance synergy and structural integrity of dissimilar alloys. Problems such as weak interface bonding and insufficient forming accuracy have become key bottlenecks restricting the upgrading of tool performance.

[0003] Traditional rotary file manufacturing often involves separately forming the cutter head and clamping post and then connecting them. Mechanical connection or conventional welding processes cannot form a stable metallurgical bond layer, resulting in low interfacial bonding strength. During high-speed rotary cutting, problems such as loosening and separation can easily occur, posing operational safety hazards. Separate manufacturing makes it difficult to accurately control the forming shrinkage characteristics of the two types of blanks, which can easily lead to deformation and cracking during sintering. The dimensional accuracy and coaxiality of the finished product are difficult to guarantee, resulting in excessive radial runout during rotation, affecting processing quality. The blanks formed by traditional pressing processes have uneven density distribution, limited interfacial bonding area, and insufficient diffusion of alloying elements, making the bonding layer prone to defects such as gaps and porosity. At the same time, traditional processes are complicated in production steps, with large subsequent machining allowances, resulting in low production efficiency and yield. They cannot simultaneously meet the requirements of cutter head wear resistance and clamping post toughness, making them unsuitable for high-load, high-precision industrial processing conditions. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a method for integrally forming a heterogeneous alloy rotary file based on cobalt diffusion. Through a complete process of powder preparation and ball milling, asymmetric vibration pressing, clean coaxial assembly, gradient vacuum sintering, and precision machining and testing, this method achieves the integrated fabrication of a cemented carbide cutting tip and a tough alloy clamping post. This method relies on the interfacial diffusion of cobalt to form a dense metallurgical bonding layer, solving problems such as weak bonding, shrinkage mismatch, and poor forming accuracy in traditional separate fabrication. It allows the wear-resistant properties of the cutting tip and the toughness of the clamping post to synergistically complement each other. The overall process simplifies production steps, improves the uniformity of blank density and the coaxiality of the finished product, and ensures the stability and structural strength of the rotary file during high-speed operation. It can be widely used in the field of precision machining, effectively improving tool service life and machining reliability, and promoting the upgrading of cutting tool manufacturing technology.

[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a method for integral forming of a heterogeneous alloy rotary file based on cobalt diffusion, the specific steps of which are as follows:

[0006] S1, Powder preparation and ball milling: Prepare WC-Co cemented carbide cutter head powder and Ni-Co-based toughness alloy clamping column powder. The cutter head powder has a cobalt content of 6%-10% and a particle size of 0.5-1.5μm, while the clamping column powder has a cobalt content of 15%-20% and a particle size of 2-5μm. They are vacuum ball milled separately under argon protection, with a ball-to-material ratio of 5:1, a rotation speed of 200-300r / min, and a duration of 2-4h. After ball milling, they are dried and sieved.

[0007] S2, Asymmetric Vibration Pressing: Powder molding superimposed with sawtooth asymmetric axial vibration, the basic static pressure of the cutter head preform is 150-200MPa, the basic static pressure of the clamping column preform is 100-150MPa, the vibration waveform has a pressure rate of 50-100MPa / s in the rising segment and 10-20MPa / s in the falling segment, a frequency of 20-50Hz, and an amplitude of 5%-15% of the basic static pressure. It presses out a cutter head preform with a three-stage stepped concave structure and a clamping column preform with corresponding bosses. The absolute value of the difference in sintering shrinkage between the two is ≤0.3%, and the green density is 55%-60% of the theoretical density.

[0008] S3, Coaxial Assembly and Cleaning: The cutter head preform and the clamping column preform are coaxially fitted together with an assembly gap of 0.05-0.1mm and a coaxiality error of ≤0.02mm. The assembly interface is ultrasonically cleaned with anhydrous ethanol and dried with nitrogen.

[0009] S4, Gradient Vacuum Sintering: The assembled blank is placed in a vacuum furnace at a pressure ≤ 1×10⁻⁶. -2 Pa, heat to 800℃ at 5-10℃ / min and hold for 1-2 hours, then heat to 1350-1450℃ at 2-5℃ / min and hold for 2-4 hours, then cool with the furnace;

[0010] S5, Precision Machining and Inspection: The sintered blank is deburred by CNC grinding to remove the oxide layer, and the cutting edge and shank are precision machined. The finished product dimensions, interface structure and high-speed rotation parameters are inspected.

[0011] Further, in step S1, the WC-Co cemented carbide tip powder is prepared by reduction carbide method, wherein the WC phase is an equiaxed single crystal structure and the cobalt phase is electrolytic spherical cobalt powder; the Ni-Co based tough alloy clamping column powder is prepared by vacuum atomization method, wherein the oxygen content of the powder is not higher than 200ppm and the sphericity is not lower than 92%.

[0012] Furthermore, in step S1, the ball milling process uses cemented carbide balls as grinding balls, with a mass ratio of 6mm, 10mm, and 15mm diameter grinding balls of 1:2:1. During ball milling, 1.5%-2% of paraffin forming agent and 0.1%-0.2% of stearic acid lubricant by total powder mass are added. The ball mill jar is first evacuated to ≤1×10⁻⁶. -1 Pa, then fill with high-purity argon gas until the gauge pressure is 0.05-0.15 MPa.

[0013] Furthermore, in step S1, during the ball milling process, the machine is stopped and cooled for 3-7 minutes every 20-40 minutes, and the temperature inside the ball milling jar is controlled below 45°C; the powder after ball milling is dried in a vacuum environment at a constant temperature of 55-65°C for 1.5-2.5 hours, and then sieved through a 180-250 mesh stainless steel sieve.

[0014] Furthermore, in step S2, the surface roughness Ra of the mold cavity used for pressing and forming is ≤0.02μm, the height of the three-stage stepped concave structure of the cutter head preform is 0.5mm, 1.0mm and 0.5mm respectively, the diameter decreases by 0.3mm respectively, and the radius of the stepped fillet R is 0.1mm, where R represents the fillet radius.

[0015] Furthermore, in step S2, when the preform is pressed, a pre-pressure is first applied. The pre-pressure of the cutter head is 40-60MPa, the pre-pressure of the clamping column is 25-35MPa, the pre-pressure is held for 3-7 seconds, the vibration pressing time is 10-20 seconds, the pressure is held for 10-30 seconds after the vibration ends, and the pressure is released and demolded at a rate of 5-10MPa / second.

[0016] Furthermore, in step S3, the preform assembly is carried out in a dust-free environment with an ambient temperature of 20-25℃, a relative humidity of 40%-60%, an ultrasonic cleaning power of 100-200W, a frequency of 30-50kHz, a duration of 5-10 minutes, and a nitrogen drying pressure of 0.15-0.25MPa.

[0017] Furthermore, in step S4, the vacuum sintering employs a horizontal vacuum molybdenum wire sintering furnace, and the assembled preforms are placed vertically within a graphite boat, with a spacing of not less than 10 mm between the preforms; during the degreasing and pre-sintering stage, the furnace pressure is maintained at 1×10⁻⁶. -1 Pa to 1×10 -2 Pa; During the high-temperature diffusion sintering stage, the furnace pressure should not exceed 1×10 Pa. -2 Pa.

[0018] Furthermore, in step S5, the sintered blank is rough ground using a CNC cylindrical grinder to remove 0.1-0.2mm of machining allowance, and then fine ground using a five-axis CNC tool grinder. The cutting edge size accuracy is controlled within ±0.02mm, and the fillet radius R is 0.02-0.05mm.

[0019] Furthermore, in step S5, a coordinate measuring machine is used to detect the dimensions of the finished product, a field emission scanning electron microscope is used to observe the interface diffusion layer structure, and a laser displacement sensor is used to detect the radial runout and vibration amplitude under high-speed rotation.

[0020] Compared with existing technologies, this method for integral forming of a heterogeneous alloy rotary file based on cobalt diffusion has the following advantages:

[0021] I. This invention utilizes a powder system combining a carbide cutting tip and a tough alloy clamping post, along with a proprietary ball milling process to enhance powder uniformity and formability. Asymmetric vibration pressing technology is employed to prepare a matched, interlocking preform, precisely controlling the shrinkage characteristics of the two types of preforms to prevent deformation and cracking during sintering. A stepped interlocking structure increases the interfacial bonding area, and gradient vacuum sintering achieves full interfacial diffusion of cobalt, forming a continuous, dense transition layer in the bonding area. This eliminates interfacial gaps and weak points, organically integrating the high hardness and wear resistance of the cutting tip with the high toughness and bending resistance of the clamping post. The one-piece molding process eliminates the traditional secondary connection steps, ensuring assembly coaxiality and interfacial bonding stability, improving the structural stability of the rotary file during high-speed rotation, optimizing cutting performance, extending the overall tool life, simplifying production processes, and enhancing the reliability of the machining process.

[0022] II. This invention improves powder purity, formability, and dispersibility by optimizing powder preparation and post-processing. High-precision molds and pressing processes ensure dimensional accuracy and structural uniformity of the preform. Clean coaxial assembly and interface cleaning processes eliminate impurities that could affect interface bonding quality. The vacuum sintering process involves phased control of the furnace environment, simultaneously completing degreasing and diffusion sintering to prevent oxidation and deformation of the blank, ensuring a uniform and dense interface diffusion layer. Subsequent precision machining accurately controls the dimensional accuracy of the cutting edge and shank. Multi-dimensional testing methods comprehensively verify the performance of the finished product, effectively reducing processing defects and the defect rate. The dissimilar alloy interface achieves metallurgical bonding through cobalt diffusion, resulting in significantly superior bonding strength compared to traditional connection methods. This ensures the wear resistance and durability of the cutting head during operation while enhancing the impact and fatigue resistance of the clamping posts, making it suitable for demanding high-speed machining conditions and improving tool safety and processing efficiency.

[0023] Other advantages, objectives and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination or study, or may be learned from the practice of the invention. Attached Figure Description

[0024] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without any creative effort.

[0025] Figure 1 This is a flowchart of the integral molding process of a heterogeneous alloy rotary file based on cobalt diffusion. Detailed Implementation

[0026] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with the accompanying drawings and preferred embodiments, is provided below.

[0027] Example 1:

[0028] A method for integral forming of a heterogeneous alloy rotary file based on cobalt diffusion, the specific steps of which are as follows: Figure 1 As shown.

[0029] S1. Powder Preparation and Ball Milling: WC-Co cemented carbide cutting tool powder was prepared using a reduction carbide method. The WC phase was an equiaxed single-crystal structure, and the cobalt phase was electrolytically spherical cobalt powder. The powder contained 8% cobalt and had an average particle size of 1 μm. Ni-Co-based toughness alloy clamping column powder was prepared using a vacuum atomization method. The powder contained 18% cobalt, had an average particle size of 3 μm, an oxygen content of 180 ppm, and a sphericity of 94%. Both powders were subjected to vacuum ball milling. A horizontal vacuum ball mill jar was used, and cemented carbide grinding balls with diameters of 6 mm, 10 mm, and 15 mm were mixed in a mass ratio of 1:2:1, with a ball-to-powder ratio of 5:1. Before ball milling, 1.8% of the total powder mass of paraffin molding agent and 0.15% of the total powder mass of stearic acid lubricant were added to the ball mill jar, and the jar was evacuated to a vacuum level of 1 × 10⁻⁶. -1 Pa, then purge with high-purity argon until the gauge pressure reaches 0.1 MPa. Set the ball mill speed to 250 r / min, with a total milling time of 3 hours. During the milling process, stop the mill for 5 minutes every 30 minutes to cool it down, and maintain the temperature inside the milling jar below 45℃ throughout the process. After milling, place the powder in a vacuum drying oven and dry at 60℃ for 2 hours. After drying, sieve it through a 200-mesh stainless steel sieve for later use.

[0030] S2, Asymmetric Vibration Pressing: The mold used for pressing is made of ultra-fine grain cemented carbide, with a mold cavity surface roughness Ra≤0.02μm. The preform is pressed using a combination of powder molding and sawtooth asymmetric axial vibration. First, a pre-pressure of 50MPa is applied to the cutter head powder and held for 5 seconds. Then, a base static pressure of 180MPa is set. The vibration waveform has an upward pressure rate of 80MPa / s and a downward pressure rate of 15MPa / s, a vibration frequency of 35Hz, and an amplitude of 10% of the base static pressure. The vibration pressing time is 15 seconds, followed by a 20-second pressure hold. Demolding is then performed at a rate of 8MPa / s, resulting in a cutter head preform with a three-stage stepped concave structure. The heights of the three-stage stepped concave structures are 0.5mm, 1.0mm, and 0.5mm respectively, with diameters decreasing by 0.3mm each, and a step fillet radius R of 0.1mm. The same pressing mold was used to preform the clamping column powder. A pre-compression pressure of 30 MPa was applied and held for 5 seconds. Then, a base static pressure of 120 MPa was set. The vibration waveform had a rising pressure rate of 70 MPa / s and a falling pressure rate of 15 MPa / s, a vibration frequency of 35 Hz, and an amplitude of 10% of the base static pressure. The vibration pressing time was 15 seconds, followed by a 20-second pressure hold. The pressure was then released at a rate of 8 MPa / s to demold, resulting in a clamping column preform with corresponding boss structures. The absolute difference in sintering shrinkage between the obtained cutter head preform and the clamping column preform was 0.2%, and the green density was 58% of the theoretical density.

[0031] S3, Coaxial Assembly and Cleaning: Preform assembly is performed in a dust-free environment at 22℃ and 50% relative humidity. The cutter head preform and the clamping post preform are coaxially fitted together with an assembly gap of 0.08mm and a coaxiality error of ≤0.02mm. The assembly interface is ultrasonically cleaned with anhydrous ethanol at a power of 150W, a frequency of 40kHz, and a duration of 8 minutes. After cleaning, it is dried with high-purity nitrogen gas at a pressure of 0.2MPa to obtain the assembled blank.

[0032] S4, Gradient Vacuum Sintering: The assembled blanks are placed vertically in a graphite boat with a spacing of 12mm between them, and then placed in a horizontal vacuum molybdenum wire sintering furnace for gradient vacuum sintering. The furnace pressure is first reduced to ≤1×10⁻⁶. -2 The temperature was increased to 800℃ at a heating rate of 8℃ / min and held for 1.5 hours. During this degreasing and pre-sintering stage, the pressure inside the furnace was maintained at 5×10⁻⁶ Pa. -2 Pa. The temperature is then increased to 1400℃ at a rate of 3℃ / min and held for 3 hours. During this high-temperature diffusion sintering stage, the furnace pressure is maintained at 8×10⁻⁶ Pa. -3 Pa. After the heat preservation is completed, the billet is cooled to room temperature with the furnace, and the sintered billet is taken out.

[0033] S5, Precision Machining and Inspection: The sintered blank is rough-ground using a CNC cylindrical grinder to remove a 0.15mm machining allowance, surface oxide layer, and burrs. A five-axis CNC tool grinder is then used for finish grinding, machining the cutting edge and shank of the tool head. The dimensional accuracy of the cutting edge is controlled within ±0.02mm, and the corner radius R is controlled within 0.03mm. A coordinate measuring machine is used to inspect the overall dimensional accuracy of the finished product. A field emission scanning electron microscope is used to observe the interface diffusion layer structure. A laser displacement sensor is used to detect the radial runout and vibration amplitude of the finished product at a high-speed rotation of 30,000 r / min.

[0034] Example 2:

[0035] Interface characterization of heterogeneous alloy molded bodies and feasibility verification of integral molding process.

[0036] Sample Preparation: Based on the process of Example 1, three parallel experiments were conducted, with only the interlocking structure parameters of the preforms changed; all other process parameters remained identical to those in Example 1. The first group employed a three-tiered concave interlocking structure, with step heights of 0.5 mm, 1.0 mm, and 0.5 mm, and diameters decreasing by 0.3 mm, with a step fillet radius R of 0.1 mm. The second group employed a two-tiered concave interlocking structure, with step heights of 1.0 mm and 1.0 mm, and diameters decreasing by 0.3 mm, with a step fillet radius R of 0.1 mm. The third group employed a single-tiered concave interlocking structure, with a step height of 2.0 mm, diameters decreasing by 0.3 mm, and a step fillet radius R of 0.1 mm. All three groups of experiments were prepared using the powder ball milling, pressing, coaxial assembly, and vacuum sintering process described in Example 1, yielding the corresponding sintered samples.

[0037] Interface structure and performance characterization: The morphology of the interface region of the three groups of sintered samples was observed using field emission scanning electron microscopy, and the thickness of the interface diffusion layer and the interface defects were recorded. Energy dispersive spectroscopy (EDS) was used to perform continuous line scanning analysis of the cobalt distribution in the interface region to confirm the uniformity of element diffusion. The interfacial shear strength of the three groups of samples was tested using a universal testing machine, with five parallel samples tested in each group, and the final result was the arithmetic mean. The sintering shrinkage rate of the cutter head and clamping column of the three groups of samples was measured using a high-precision dimensional measuring instrument, and the absolute value of the difference between the two shrinkage rates was calculated.

[0038] Feasibility verification results statistics and analysis:

[0039] The core performance test results of the three groups of samples are shown in the table below.

[0040] Table 1. Test results of core performance of specimens with different interlocking structures

[0041]

[0042] Results Analysis: The three-stage stepped concave structure specimens exhibited the thickest interfacial diffusion layer, the most complete cobalt diffusion, and significantly higher interfacial shear strength than the two-stage and single-stage stepped structure specimens. Simultaneously, they showed the smallest absolute difference in sintering shrinkage, the best dimensional consistency of the sintered blank, and no pores or cracks in the interfacial region. The two-stage stepped concave structure specimens showed moderate interfacial diffusion and bonding performance, with only minor gaps and no obvious cracks, meeting basic usage requirements. The single-stage stepped concave structure specimens showed insufficient interfacial element diffusion, the thinnest diffusion layer, the lowest interfacial bonding strength, the largest difference in sintering shrinkage, and obvious boundary cracks at the interface, resulting in poor integral molding bonding. The experimental results confirm that the three-stage stepped concave interlocking structure can effectively improve the bonding performance of dissimilar alloy interfaces, reduce the shrinkage difference during sintering, ensure the feasibility and stability of the integral molding process, and provide a structural foundation for the long-term stable use of rotary file finished products.

[0043] Example 3:

[0044] Optimization of powder preparation and ball milling process parameters.

[0045] Experimental Design: Based on the process of Example 1, four parallel experiments were set up. Only three core parameters were adjusted: cobalt content of the cutter head powder and the clamping column powder, ball milling speed, and total ball milling time. All other process parameters were completely consistent with those of Example 1. The parameter settings of the four experimental groups were all within the preset process range. The parameters of Experiment 1 were completely consistent with those of Example 1. The corresponding parameters of Experiments 2, 3, and 4 were adjusted respectively. All experiments were carried out according to the process of Example 1 to complete the powder ball milling and preform preparation.

[0046] Performance testing indicators: The average particle size and particle size distribution width of the ball-milled powder were measured using a laser particle size analyzer, and the particle size uniformity of the powder was recorded. The oxygen content of the ball-milled powder was measured using an oxygen-nitrogen analyzer to assess the degree of oxidation of the powder. The loose pack density of the powder was measured using a bulk density tester to assess the powder's molding performance. The green density of the preform was measured using the Archimedes' displacement method, and the ratio of green density to theoretical density was calculated. Five parallel samples were tested in each group of experiments, and the final result was the arithmetic mean.

[0047] Optimize the statistical analysis of experimental results:

[0048] The parameter settings and performance test results for the four groups of experiments are shown in the table below.

[0049] Table 2. Test results of powder and preform properties under different ball milling process parameters.

[0050]

[0051] Results Analysis: Group 1 exhibited the best overall performance, with uniform and moderate powder particle size, low oxygen content, and preform green density within the ideal range. The powder's formability and sintering compatibility were the best. Group 2 had the lowest ball milling speed and shortest milling time, the coarsest powder particle size, and the lowest oxygen content, but also the lowest green density, resulting in insufficient powder formability and increased difficulty in subsequent sintering densification. Group 3 had the highest ball milling speed and longest milling time, resulting in the finest powder particle size, but a significantly increased oxygen content, leading to obvious oxidation and agglomeration. Although it had the highest green density, the excessive oxygen content caused porosity defects during subsequent sintering, affecting the alloy's final mechanical properties. Group 4's performance was at a moderate level, with powder particle size, oxygen content, and green density all meeting basic formability requirements, but its overall performance was inferior to Group 1. The experimental results confirm that the ball milling process parameters used in Example 1 can effectively control the degree of powder oxidation while ensuring powder particle size uniformity, obtaining alloy powder with excellent formability, providing a high-quality raw material foundation for subsequent pressing and sintering processes.

[0052] Example 4:

[0053] Optimization of asymmetric vibration pressing process parameters.

[0054] Experimental Design: Based on the process of Example 1, four parallel experiments were set up. Only three core parameters—the basic static pressure vibration frequency, vibration waveform, and pressure rise / fall rate of the preform of the cutter head and clamping column—were adjusted. All other process parameters were completely consistent with those of Example 1. The parameter settings for all four experiments were within the preset process range. The parameters of Experiment 1 were completely consistent with those of Example 1, while the corresponding parameters for Experiments 2, 3, and 4 were adjusted respectively. All experiments followed the process of Example 1 to complete the preform pressing and subsequent sintering processes.

[0055] Performance testing indicators: The green density of the preform was tested using the Archimedes' displacement method, and the ratio of green density to theoretical density was calculated. The dimensional accuracy of the preform was tested using a high-precision dimensional measuring instrument, and the absolute value of the shrinkage difference between the cutter head and the clamping post after sintering was recorded. The appearance of the preform and sintered green body was observed using a stereomicroscope, and the forming defect rate was statistically analyzed, including delamination, edge chipping, and microcracks. The flexural strength of the sintered samples was tested using a universal testing machine to evaluate the mechanical properties of the green body. Five parallel samples were tested in each group of experiments, and the final result was the arithmetic mean.

[0056] Optimize the statistical analysis of experimental results:

[0057] The parameter settings and performance test results for the four groups of experiments are shown in the table below.

[0058] Table 3. Test results of molding effect under different vibration pressing process parameters

[0059]

[0060] Results Analysis: Group 1 exhibited the best overall forming effect, with the preform green density within the ideal range, the smallest difference in shrinkage between the cutter head and clamping column after sintering, no forming defects, the highest flexural strength after sintering, and the most excellent mechanical properties. Group 2 had the lowest basic static pressure, the slowest vibration frequency, and the lowest pressure increase / decrease rate. It also had the lowest preform green density, the largest difference in sintering shrinkage, a higher forming defect rate, insufficient green body densification, and poor final mechanical properties. Group 3 had the highest basic static pressure, the fastest vibration frequency, and the highest pressure increase / decrease rate. Although it had the highest green density, the rapid pressure change and high-frequency vibration caused mold resonance, resulting in the highest probability of defects such as lamination and microcracks in the preform. Abnormal grain growth occurred after sintering, and the flexural strength decreased significantly. Group 4's performance was at a moderate level, with a low forming defect rate, meeting the basic forming requirements. However, its green density uniformity and final mechanical properties were inferior to Group 1. The experimental results confirm that the asymmetric vibration pressing molding process parameters used in Example 1 can effectively improve the green body density and density uniformity of the preform, reduce the difference in sintering shrinkage rate, reduce the molding defect rate, and finally obtain a sintered green body with excellent mechanical properties.

[0061] Example 5:

[0062] Optimization of gradient vacuum sintering process parameters.

[0063] Experimental Design: Based on the process of Example 1, four parallel experiments were set up. Only three core parameters were adjusted: high-temperature sintering temperature, high-temperature holding time, and the heating rate from low to high temperature. All other process parameters were completely consistent with those of Example 1. The parameter settings of the four experiments were all within the preset process range. The parameters of Experiment 1 were completely consistent with those of Example 1, while the corresponding parameters of Experiments 2, 3, and 4 were adjusted respectively. All experiments completed the vacuum sintering and subsequent processing steps according to the process of Example 1.

[0064] Performance testing indicators: The density of the sintered samples was tested using the Archimedes' displacement method, and the relative density was calculated. The metallographic structure of the alloy was observed using a field emission scanning electron microscope, and the average size of the WC grains and the thickness of the interfacial diffusion layer were recorded. The hardness of the cutting edge area was tested using a Rockwell hardness tester, and the bending strength and interfacial shear strength of the samples were tested using a universal testing machine. Five parallel samples were tested in each group of tests, and the final results were the arithmetic mean.

[0065] Optimize the statistical analysis of experimental results:

[0066] The parameter settings and performance test results for the four groups of experiments are shown in the table below.

[0067] Table 4. Alloy property test results under different sintering process parameters

[0068]

[0069] Results Analysis: Group 1 exhibited the best overall performance. The sintered sample had a relative density approaching full density, with uniform and moderate WC grain size, and the interfacial diffusion layer thickness was within the ideal range. The hardness, bending strength, and interfacial shear strength of the cutting head all reached the highest levels, balancing the high hardness of the cutting head with the high toughness of the clamping post, while simultaneously achieving a high-strength interfacial bond. Group 2 had the lowest sintering temperature, shortest holding time, and slowest heating rate. It suffered from insufficient alloy densification, the lowest relative density, inadequate diffusion of interfacial elements, and the thinnest diffusion layer. Ultimately, its hardness and mechanical properties were poor, failing to meet the requirements for rotary files. Group 3 had the highest sintering temperature, longest holding time, and fastest heating rate. Although the alloy density was high, significant abnormal growth of WC grains led to a decrease in cutting head hardness and bending strength. Simultaneously, the excessive growth of the interfacial diffusion layer eliminated the performance gradient between the cutting head and the clamping post, resulting in a decrease in interfacial bond strength. Group 4's performance was at a moderate level. The alloy density and mechanical properties met basic usage requirements, but its overall performance was inferior to Group 1. The experimental results confirm that the gradient vacuum sintering process parameters used in Example 1 can achieve full densification of the alloy, while controlling grain growth and promoting uniform diffusion of interfacial elements, thus obtaining a heterogeneous alloy sintered body that balances hardness, toughness and interfacial bonding strength, providing a guarantee for the excellent performance of the rotary file product.

[0070] Example 6:

[0071] Verification of the overall performance and service stability of the finished rotary file.

[0072] Sample preparation: Based on the optimal process parameters of Example 1, 10 batches of finished rotary files were continuously prepared, and 10 samples were randomly selected from each batch for performance testing. A control group was also set up, in which dissimilar alloy rotary files of the same specifications were prepared using a conventional welding process. The powder material of the cutting head and clamping post was completely consistent with that of Example 1, and the finished product dimensions were exactly the same as those of the samples prepared by this method.

[0073] Performance testing items: A coordinate measuring machine (CMM) was used to check the dimensional accuracy of the finished product, recording the cutting edge dimensional deviation and shank radial runout. A laser displacement sensor was used to detect the radial runout and vibration amplitude of the finished product under high-speed rotation at 30,000 r / min and 60,000 r / min. A CNC cutting testing machine was used for continuous cutting tests on the material 45# steel, with cutting parameters of 30,000 r / min rotation speed, 0.1 mm / r feed rate, and 0.5 mm depth of cut. The cutting edge wear and failure status were recorded after 10 hours of continuous cutting. A high-low temperature cycling test was used to test the service stability of the finished product. The cycling temperature ranged from -20℃ to 120℃, with each cycle lasting 4 hours, for a total of 20 cycles. The retention rate of interfacial bonding strength after the cycles was tested. Performance data from 10 batches of finished products were statistically analyzed, and the relative standard deviation between batches was calculated to evaluate batch stability.

[0074] Performance test results statistics and analysis:

[0075] The core performance test results of the finished products prepared by this method and those prepared by traditional welding processes are shown in the table below.

[0076] Table 5 Comparison of core performance of rotary files prepared using different processes

[0077]

[0078] Results Analysis: The rotary files prepared by this method are significantly superior to those prepared by traditional welding processes in terms of dimensional accuracy, high-speed rotation stability, cutting service life, service stability, and batch consistency. Regarding dimensional accuracy, the cutting edge dimensional deviation and shank radial runout of the files prepared by this method are much smaller than those of welded files, meeting the requirements for high-precision machining. In terms of high-speed rotation performance, the radial runout and vibration amplitude of the files prepared by this method are extremely low at high speeds of 30,000 r / min and 60,000 r / min, avoiding vibration-induced chipping during high-speed rotation and significantly improving operational safety and machining accuracy. Regarding cutting service life, the files prepared by this method show minimal edge wear after 10 hours of continuous cutting, with no chipping or breakage. Their effective service life is more than three times that of welded files, thanks to the high-strength interface bonding of the integral molding process, avoiding the interface cracking and detachment problems common in welding. In terms of service stability, the files prepared by this method maintain extremely high interface strength retention after high and low temperature cycling, with no significant performance degradation, while welded files show obvious interface cracking failure and a significant decrease in strength retention. Regarding batch consistency, the finished products prepared by this method exhibit extremely small relative standard deviations in performance between batches, demonstrating excellent batch stability and meeting the needs of large-scale industrial production. Experimental results confirm that the dissimilar alloy rotary files prepared by this method possess comprehensive performance and service stability far superior to products manufactured using traditional welding processes. They are adaptable to the processing requirements of workpieces made of different materials and have excellent industrial application value.

[0079] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A method for integral forming of a heterogeneous alloy rotary file based on cobalt diffusion, characterized in that, The specific steps of this method are as follows: S1, Powder preparation and ball milling: Prepare WC-Co cemented carbide cutter head powder and Ni-Co-based toughness alloy clamping column powder. The cutter head powder has a cobalt content of 6%-10% and a particle size of 0.5-1.5μm, while the clamping column powder has a cobalt content of 15%-20% and a particle size of 2-5μm. They are vacuum ball milled separately under argon protection, with a ball-to-material ratio of 5:1, a rotation speed of 200-300r / min, and a duration of 2-4h. After ball milling, they are dried and sieved. S2, Asymmetric Vibration Pressing: Powder molding superimposed with sawtooth asymmetric axial vibration, the basic static pressure of the cutter head preform is 150-200MPa, the basic static pressure of the clamping column preform is 100-150MPa, the vibration waveform has a pressure rate of 50-100MPa / s in the rising segment and 10-20MPa / s in the falling segment, a frequency of 20-50Hz, and an amplitude of 5%-15% of the basic static pressure. It presses out a cutter head preform with a three-stage stepped concave structure and a clamping column preform with corresponding bosses. The absolute value of the difference in sintering shrinkage between the two is ≤0.3%, and the green density is 55%-60% of the theoretical density. S3, Coaxial Assembly and Cleaning: The cutter head preform and the clamping column preform are coaxially fitted together with an assembly gap of 0.05-0.1mm and a coaxiality error of ≤0.02mm. The assembly interface is ultrasonically cleaned with anhydrous ethanol and dried with nitrogen. S4, Gradient Vacuum Sintering: The assembled blank is placed in a vacuum furnace at a pressure ≤ 1×10⁻⁶. -2 Pa, heat to 800℃ at 5-10℃ / min and hold for 1-2 hours, then heat to 1350-1450℃ at 2-5℃ / min and hold for 2-4 hours, then cool with the furnace; S5, Precision Machining and Inspection: The sintered blank is deburred by CNC grinding to remove the oxide layer, and the cutting edge and shank are precision machined. The finished product dimensions, interface structure and high-speed rotation parameters are inspected.

2. The method for integral forming of a heterogeneous alloy rotary file based on cobalt diffusion according to claim 1, characterized in that, In step S1, the WC-Co cemented carbide tip powder is prepared by reduction carbide method, wherein the WC phase is an equiaxed single crystal structure and the cobalt phase is electrolytic spherical cobalt powder; the Ni-Co based tough alloy clamping column powder is prepared by vacuum atomization method, wherein the oxygen content of the powder is not higher than 200ppm and the sphericity is not lower than 92%.

3. The method for integral forming of a heterogeneous alloy rotary file based on cobalt diffusion according to claim 1, characterized in that, In step S1, the ball milling process uses cemented carbide balls as grinding balls. The mass ratio of grinding balls with diameters of 6mm, 10mm, and 15mm is 1:2:

1. During ball milling, 1.5%-2% of paraffin forming agent and 0.1%-0.2% of stearic acid lubricant by weight of the total powder are added. The ball mill jar is first evacuated to ≤1×10⁻⁶. -1 Pa, then fill with high-purity argon gas until the gauge pressure is 0.05-0.15 MPa.

4. The method for integral forming of a heterogeneous alloy rotary file based on cobalt diffusion according to claim 1, characterized in that, In step S1, during the ball milling process, the machine is stopped and cooled for 3-7 minutes every 20-40 minutes, and the temperature inside the ball milling jar is controlled below 45°C. The powder after ball milling is dried in a vacuum environment at a constant temperature of 55-65°C for 1.5-2.5 hours, and then sieved through a 180-250 mesh stainless steel sieve.

5. The method for integral forming of a heterogeneous alloy rotary file based on cobalt diffusion according to claim 1, characterized in that, In step S2, the surface roughness Ra of the mold cavity used for pressing is ≤0.02μm, the height of the three-stage stepped concave structure of the cutter head preform is 0.5mm, 1.0mm and 0.5mm respectively, the diameter decreases by 0.3mm respectively, and the radius of the stepped fillet R is 0.1mm, where R represents the fillet radius.

6. The method for integral forming of a heterogeneous alloy rotary file based on cobalt diffusion according to claim 1, characterized in that, In step S2, when the preform is pressed, a pre-pressure is first applied. The pre-pressure of the cutter head is 40-60MPa, the pre-pressure of the clamping column is 25-35MPa, the pre-pressure is held for 3-7 seconds, the vibration pressing time is 10-20 seconds, the pressure is held for 10-30 seconds after the vibration ends, and the pressure is released and demolded at a rate of 5-10MPa / second.

7. The method for integral forming of a heterogeneous alloy rotary file based on cobalt diffusion according to claim 1, characterized in that, In step S3, the preform assembly is carried out in a dust-free environment with an ambient temperature of 20-25℃, a relative humidity of 40%-60%, an ultrasonic cleaning power of 100-200W, a frequency of 30-50kHz, a duration of 5-10 minutes, and a nitrogen blowing pressure of 0.15-0.25MPa.

8. The method for integral forming of a heterogeneous alloy rotary file based on cobalt diffusion according to claim 1, characterized in that, In step S4, the vacuum sintering is performed using a horizontal vacuum molybdenum wire sintering furnace. The assembled preforms are placed vertically inside a graphite boat, with a spacing of not less than 10 mm between the preforms. During the degreasing and pre-sintering stage, the furnace pressure is maintained at 1×10⁻⁶. -1 Pa to 1×10 -2 Pa; During the high-temperature diffusion sintering stage, the furnace pressure should not exceed 1×10 Pa. -2 Pa.

9. The method for integral forming of a heterogeneous alloy rotary file based on cobalt diffusion according to claim 1, characterized in that, In step S5, the sintered blank is rough ground using a CNC cylindrical grinder to remove 0.1-0.2mm of machining allowance, and then fine ground using a five-axis CNC tool grinder. The cutting edge size accuracy is controlled within ±0.02mm, and the fillet radius R is 0.02-0.05mm.

10. The method for integral forming of a heterogeneous alloy rotary file based on cobalt diffusion according to claim 1, characterized in that, In step S5, a coordinate measuring machine is used to detect the dimensions of the finished product, a field emission scanning electron microscope is used to observe the diffusion layer structure of the interface, and a laser displacement sensor is used to detect the radial runout and vibration amplitude under high-speed rotation.